(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The article analyzes the fact that in a volleyball game, players must move with the ball in a short time. Therefore, in order to play with the ball in a particular game situation, a player must be highly prepared. For this purpose, it is emphasized that it is necessary to take different positions to perform different movement methods.